Financing Infrastructure in the Philippines: Fiscal Landscape and Resources Mobilization - Gilberto M. Llanto; Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2014)
This study assesses the sources and levels of infrastructure financing in the Philippines for the last five years (2008-2012). The mapping of fiscal resources showed that there had been underinvestment in infrastructure. To illustrate, in 2008-2012, public infrastructure spending as a share of GDP ranged between a low of 1.40 percent to a high of 2.09 percent - a far cry from the target 5 percent of GDP over the medium term. The result of many years of infrastructure underinvestment is woefully manifested in the Philippines' place in quality-of-infrastructure ranking among ASEAN member-states; it is currently second to the bottom.Recently, there had been significant improvements in the government's fiscal position that augur well for more substantial infrastructure spending in the future. New regional sources of financing, the liquid domestic capital market, and a low interest-rate environment also present opportunities for investing in infrastructure by both the government and the private sector. However, it is not only the constrained availability of financial resources that could restrain infrastructure investments but also institutional weaknesses and, therefore, the government must firmly commit to reform policies and strengthen institutions.
Keywords: 330; infrastructure; Philippines; public-private partnership (PPP); ASEAN connectivity; fiscal landscape